Analysis of The Enforcement of The Regulation of The Minister of Trade Number 40 of 2022 Concerning The Prohibition of Imports of Used Clothing in Metro, Lampung - Sika Aulia Fitri; Hanifah Febriani (Universitas Muhammadiyah Surakarta, 2024)
In the world of commerce, thrifting is the practice of trading second-hand goods, especially clothing, offered at more affordable prices. In some countries, importing used clothing or thrifting is considered illegal and prohibited. This is reflected in the Minister of Trade Regulation No. 40 of 2022, where the import of goods such as used clothing is considered an activity that has the potential to harm many parties. In the context of import regulation, second-hand clothing is considered a dangerous good that circulates without adequate supervision. The impact can be detrimental to consumers due to the quality of the domestic industry due to unfair competition, state revenue due to lost tax potential, and the country's economy as a whole. This research aims to answer about the regulation of criminal sanctions for the prohibition of imports of used clothing regulated in Minister of Trade Regulation Number 40 of 2022 and law enforcement against cases of prohibition of imports of used clothing regulated in Minister of Trade Regulation Number 40 of 2022 in Metro. The research method used in this research is empirical juridical by analyzing social facts using theory and applicable legal provisions. The specification of this research is descriptive analytical. This research indicates that the import and trade of used clothing in Indonesia is considered a criminal offense in the economic field and is subject to criminal penalties. Law enforcement for thrifting cases in Metro is constrained to be fined thrifting entrepreneurs in Metro are the second hand of the person who directly takes the used clothes. The relationship between the thrifting entrepreneur and the party is based on the sale and purchase agreement.